1994
DOI: 10.1002/j.1460-2075.1994.tb06383.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of proteins to the thylakoids by bipartite presequences: CFoII is imported by a novel, third pathway.

Abstract: The CFoII subunit of the ATP synthase is an integral component of the thylakoid membrane which is synthesized in the cytosol with a bipartite, lumen‐targeting presequence similar in structural terms to those of imported lumenal proteins such as plastocyanin. This presequence is shown to possess a terminal cleavage site for the thylakoidal processing peptidase, but no intermediate site for the stromal processing peptidase. The integration of CFoII into the thylakoid membrane of Pisum sativum has been analysed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
98
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 30 publications
3
98
0
1
Order By: Relevance
“…1, the three thylakoid proteins share additional common features with procoat: each contains a single transmembrane span in the mature protein and the translocated regions are all negatively charged. It was thus unsurprising that initial models for the Sec-independent insertion of CF o II (25) were based on the procoat insertion model, and this study has confirmed that in one fundamental respect the insertion of PSII-W does indeed resemble that of procoat. Both proteins adopt a loop intermediate during the insertion process, strongly suggesting that the function of the PSII-W signal peptide is to provide a second hydrophobic domain which, in concert with the transmembrane segment in the mature protein, is then able to drive the translocation of the hydrophilic intervening region into the thylakoid lumen.…”
Section: Evidence That Hydrophobic Forces Drive the Insertion Of Pre-mentioning
confidence: 53%
See 3 more Smart Citations
“…1, the three thylakoid proteins share additional common features with procoat: each contains a single transmembrane span in the mature protein and the translocated regions are all negatively charged. It was thus unsurprising that initial models for the Sec-independent insertion of CF o II (25) were based on the procoat insertion model, and this study has confirmed that in one fundamental respect the insertion of PSII-W does indeed resemble that of procoat. Both proteins adopt a loop intermediate during the insertion process, strongly suggesting that the function of the PSII-W signal peptide is to provide a second hydrophobic domain which, in concert with the transmembrane segment in the mature protein, is then able to drive the translocation of the hydrophilic intervening region into the thylakoid lumen.…”
Section: Evidence That Hydrophobic Forces Drive the Insertion Of Pre-mentioning
confidence: 53%
“…Gallusser and Kuhn (32) have shown that electrostatic interactions play a critical role in the insertion of procoat, in which basic residues in both the extreme N and C termini bind to the negatively charged membrane surface; removal of either set of basic residues renders procoat wholly insertion incompetent. Like procoat, pre-CF o II contains positively charged N and C termini and a similar mechanism was considered possible for this protein (25). However, the C-terminal region of pre-PSII-W is extremely negatively charged (a series of five acidic residues follows the transmembrane section), precluding any electrostatic binding between this region and the membrane surface.…”
Section: Evidence That Hydrophobic Forces Drive the Insertion Of Pre-mentioning
confidence: 96%
See 2 more Smart Citations
“…These routes include the spontaneous insertion of proteins (18), and signal recognition particle-dependent (9), ⌬pH-dependent (6, 21), and SecA-dependent pathways (22,33). A twin-arginine motif is specifically recognized by components of the ⌬pH-dependent pathway, and hydrophobic sequences are favored by the signal recognition particle-dependent pathway (12,13).…”
mentioning
confidence: 99%